Groups with a condition of layered minimality - Polovitsky , Ya. D. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Certain generalizations of the minimal condition are considered. One of them the layer-minimal condition —enables us to obtain a new characterization of groups with Chernikov layers in the class of locally finite groups.